Analisi strutturale e caratterizzazione della necromassa in sugherete della Calabria - Barreca, L.; Marziliano, P. A.; Menguzzato, G.; Scuderi, A. (iForest - Biogeosciences and Forestry, 2010)
The cork forests are one the most interesting forest ecosystems in the Mediterranean area. Their distribution and ecological characteristics have undergone a significant transformation after the significant changes following the development and establishment of agricultural crops. Currently, only a few stands, which survive in hard to reach places, prove the wide spread distribution of this species was also in the recent past. This study describes the stand structure of some cork forests in Calabria region (southern Italy). In order, to characterize the vertical structure Latham index has been applied, while for the description of the horizontal distribution NBSI group indices has been used. Detailed surveys on dead wood were also conducted determining the occurring volume and its decay stage according to the decay classes system proposed by Hunter. The aim of this study is to provide guidelines for sustainable management of cork forests, improving and promoting the structural complexity and functional efficiency of these forest stands.
The following values have no corresponding Zotero field: pub-location: Dipartimento Gestione dei Sistemi Agrari e Forestali (GESAF), Universit degli studi Mediterranea di Reggio Calabria, Localit Feo di Vito, I-89060 Reggio Calabria (Italia) publisher: SISEF - Italian Society of Silviculture and Forest Ecology
Keywords: Dead Wood; Quercus Suber L; Stand Structure; Structural Index; Sustainable Forest Management